Case Report: A rare successful case of treating cerebral air embolism following the removal of a central venous catheter without intracardiac structural abnormalities - Song, Mingzhe; Wang, Wenxiang; Wu, Jie (Frontiers in Surgery, 2025)
BackgroundCerebral air embolism following the removal of a central venous catheter is a rare and often fatal complication, resulting in severe neurological deficits and potentially death.Case presentationWe report a unique case involving a 57-year-old male, where the postoperative removal of a central venous catheter resulted in cerebral air embolism in a patient with esophageal cancer who had no intracardiac structural abnormalities. Following treatment that included low-temperature brain protection and the reduction of cerebral edema, a favorable prognosis was achieved.ConclusionsThis case underscores the efficacy of prompt low-temperature brain protection in managing cerebral air embolism. Additionally, it examines potential mechanisms underlying cerebral air embolism in the absence of intracardiac structural abnormalities.